Centovalli-Centoricordi. Intervista a Oliviero Giovannoni - Krizia Bonaudo; Demis Quadri (Geography Notebooks, 2021)
Centovalli-Centoricordi was a travelling theatre show dedicated to the Centovalli that revolved around the red thread of the Centovallina, a fascinating railway track, and was born from a dream of clown Dimitri. The project was a production (in two different editions: 2013 and 2019) of the Werkstatt für Theater in collaboration with the Teatro Dimitri in Verscio and the Ferrovia Vigezzina-Centovalli. In the interview, rhythm teacher, musician and composer Oliviero Giovannoni, former teacher at the Accademia Teatro Dimitri, talks about the experience with particular reference to the sound and space dimension.